Parenting and production of anxiety on social media: Analysis of parenting on Instagram @parentalk.id - Machmiyah, Siti; Udasmoro, Wening; Noviani, Ratna (Journal of Social Studies (JSS), 2024)
This article discusses the phenomena parenting of the anxiety production constructed by @parentalk.id as a result of interacting with parenting social media accounts. In the digital era, social media has become a primary source of information for many parents seeking guidance and support in raising their children. However, the content often emphasizes ideal standards of parenting that can trigger feelings of anxiety among parents. This study uses a qualitative approach with critical multimodal discourse analysis of the Instagram social media account @parentalk.id. The research findings show that the Instagram account @parentalk.id generates anxiety among parents through its content, which portrays ideal parenting standards. The account acts as a "regime" that limits parents' freedom, guiding them towards the account's constructed ideas of ideal parenting. The account also shapes the parenting narrative by disciplining the parents themselves. Uncertainty in modernity is also used as a tool to produce anxiety in parenting. Additionally, the study found that child health is a key content theme that can trigger anxiety among parents.